MICROHYDRO POWER PLANT DESIGN IN WAILELA RUMAH TIGA VILLAGE AMBON - DJON KAFIANE ELWARIN; DENNY R. PATTIAPON; DANIEL PESURNAY; JOHANIS LEUWOL (CV KULTURA DIGITAL MEDIA, 2023)
This micro hydro power plant plan is located in Rumah Tiga Village which utilizes the Wailela river water flow. In this study, the measurement of the water discharge used the floating method and the measurement of the height of the drop used the water fitting method. From the measurement of water discharge and water fall height, it is used to determine the MHP design, which includes the dimensions of the rapid pipe, the type of water turbine, the dimensions of the water turbine, and to determine the capacity of the 3-phase synchronous generator according to the design of the PLTMH Sungai Wailela. The results of the calculation show that the theoretical power potential that can be generated at PLTMH Gunung Sawur 3 is 4.06 kW with a water flow rate of 0.225 m3 / s. and the height of falling clean water (head nett) 3.65 meters. From the water discharge and the height of the water fall, a rapid pipe design with a length of 20 meters and a diameter of 0.345 meters is obtained and a turbine dimension with a diameter of 35 cm and a width of 171 cm. From the calculation of the generated power of 4.06 kW, the capacity of the 3-phase synchronous generator used is 5 kVA with a load control system using ELC with a capacity of below 5 kW.